Analisis Pemanfaatan Akun Bisnis Instagram dalam Peningkatan Penjualan pada Gerai XYZ.Co - Rika Kharlina Ekawati (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2020)
This study aims to analyze the use of Instagram as a social media which is currently one of the most widely used social media by internet users around the world. Instagram has added a service feature that allows users to change personal accounts into business accounts for services for businesses to promote their products. This also underlies the XYZ.Co Outlet which has activated the Instagram business account feature to be able to market its products and reach wider consumers. Utilizing a business account through the Insight feature on Instagram really helps XYZ.Co Outlets to view and monitor the activities and detailed information of its followers, Instagram follower growth, product posting information most preferred by Instagram users, to promotional media offered by Instagram with promotional time and the radius of consumer distance that can be reached by users. By using descriptive qualitative analysis methods, obtained data that from the utilization of Instagram business account feature, XYZ Outlets have posted an increase in sales transactions per period, starting from October 2019 to April 2020. The results showed that there was an increase in the number of transactions per period that followed by sales that continued to increase throughout the study period.